Levinas, Løgstrup, and the Idea of Command. (9th January 2020) - Morgan, Michael L
Abstract: Robert Stern has argued that Levinas is a kind of command theorist and that, for this reason, Løgstrup can be understood to have provided an argument against Levinas. In this paper, I discuss Levinas's use of the vocabulary of demand, order, and command in the light of Jewish philosophical accounts of such notions in the work of Martin Buber, Franz Rosenzweig, and Emil Fackenheim. These accounts revise the traditional Jewish idea of command and I show that Levinas's use of this vocabulary is also revisionary. I show that in light of this tradition of discussion, Levinas's use is not susceptible to the interpretation Stern proposes and thus that the Løgstrup-style argument cannot be used against Levinas.